Cognitive and Affective Dimensions of Legal Awareness [Dimensi Kognitif dan Afektif Kesadaran Hukum] - Syuhada Syuhada (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: The success and failure of an organization/institution/social society and the law cannot be separated from the quality of the Human Resources/Human Resources who run it. The willingness of citizens to obey the law without coercion turned out to be a prerequisite for the realization of the law significantly. Therefore, the quality of Human Resources is the key to the success of the program to foster legal awareness in the community, which is then supported by a legal system that meets philosophical, juridical, and sociological aspects. The combination of the two resulted in a significant change from legal compliance to legal obedience and/or from legal knowledge to legal action. Abstrak: Kesuksesan dan kegagalan suatu organisasi/institusi/sosial masyarakat dan hukum, tidak lepas dari kualitas SDM / Human Resourse yang menjalankannya. Kesediaan warga untuk menaati hukum tanpa paksa ternyata merupakan prasyarat terealisasinya hukum secara signifikan. Oleh karena itu, kualitas Sumber Daya Manusia adalah kunci sukses program menumbuhkan kesadaran hukum di masyarakat, kemudian didukung oleh sistem hukum yang memenuhi aspek filosofis, yuridis dan sosiologis. Perpaduan keduanya menghasilkan perubahan signifikan dari sebatas legal compliance berubah menjadi legal obedience dan/atau dari legal knowledge berubah menjadi legal action.